2016
DOI: 10.5539/ibr.v9n4p100
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Silence: A Barrier to Job Engagement in Successful Organizations

Abstract: Purpose: Although the phenomenon of Organizational Silence (OS) is widely seen in organizations, there is little empirical evidence regarding its nature and components. The purpose of this research is to identify the types of OS and its effects on JE at Menoufia University Hospitals in Egypt.Design/methodology/approach: To assess OS, refer to (OS questionnaire, Schechtman, 2008;Brinsfield, 2009) and JE (JE questionnaire, Rich et al., 2010). Five dimensions of OS are constructed and measured in order to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
4
16
0
4
Order By: Relevance
“…Moreover, accord-ing to Wang et al, [59] explained that the employees might have chosen to stay silent outweighing the risks associated with being labeled a trouble-maker or being looked down upon by the leaders or fellow co-workers. Also, Nafei [29] reported that the employee silence is considered as particular conduct in which employee chooses to remain quiet and halts giving their view in an organization to remain harmless from any negative results.…”
Section: Results Regarding the Three Dimensions Of Organizationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, accord-ing to Wang et al, [59] explained that the employees might have chosen to stay silent outweighing the risks associated with being labeled a trouble-maker or being looked down upon by the leaders or fellow co-workers. Also, Nafei [29] reported that the employee silence is considered as particular conduct in which employee chooses to remain quiet and halts giving their view in an organization to remain harmless from any negative results.…”
Section: Results Regarding the Three Dimensions Of Organizationalmentioning
confidence: 99%
“…(1) support of silence by top management due to the supervisors' fears of getting negative reactions or their underlying beliefs, (2) lack of communication opportunities, (3) support of supervisor for silence, (4) official authority and (5) employees' fears of getting negative reactions. [29] Organizational silence hurts both the organization and the employees, because it makes them feel that they are not important, are not under control, and that they have lost their confidence, which causing lower levels of employee commitment, internal conflicts, reducing decision-making, and preventing positive or negative reactions to management. It also causes employee demoralization and motivation, absenteeism, and delay which negatively affect individual and organizational activities.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of organizations silence can influence both organizations and employees meanly. Employee Silence occasions unpleasant moods like dissatisfaction, cynisizm, lack of communication and stress (Nafei, 2016). In other words, if voice is refrained proficiency and employee's mentality may be substantially offended.…”
Section: Literature Review On Employee Silencementioning
confidence: 99%
“…Employee silence is a behavior in which employees lack their own actions, apprehensions and recommendations relating to their assigned work (Bastug et al, 2016). Employee silence is a behavior in which employee opts to remain quiet and stops giving opinion in an organization in order to remain safe from consequential outcomes (Nafei, 2016)…”
Section: Absorptionmentioning
confidence: 99%
“…Employee silence is significantly and negatively influenced by psychological empowerment and is significantly and negatively influencing work engagement probably assuming a role of mediator between psychological empowerment and work engagement (Nafei, 2016;Zikai, 2018). In this study relationship of psychological empowerment with work engagement in presence of a mediating varible employee silence is explored in public sector organizations in Sindh.…”
mentioning
confidence: 99%